Cognitive function and work resilience of healthcare professionals: A comparative cross-sectional study - Shaimaa A. A. M. Amer; Ahmed M. Fouad; Mohamed El-Samahy; Maha Anan; Abdullah A. Saati; Anas A. Sarhan; Samar A. Alalfy; Mirella Y. Tawfik (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Healthcare professionals (HCPs) face a variety of work-related stressors that have impact on their mental health and cognitive performance. Work resilience is a psychological resource that helps workers cope with stress and prevents unfavorable psychological impact. The aim of this study was to assess the associations between working as HCPs and cognitive function as well as work resilience. MATERIALS AND METHODS: This was a comparative cross-sectional study conducted among HCPs at Suez Canal University Hospital in Ismailia Governorate, Egypt, during April 2023 to August 2023. Two hundred and thirty-five HCPs and 107 administrative employees (Admins) were invited to participate in this study. A self-administered questionnaire was used to obtain sociodemographic and other relavent data. Cognitive function was assessed with the Mini-Mental State Examination test; work resilience was assessed with the Brief Resilience Scale; and psychological distress was measured with the Depression, Anxiety, and Stress Scale - 21-items (DASS-21) scale. Statistical significance was determined by Mann Whitney U-test for continuous variables, and Chi-square test or Fisher's exact, as appropriate, for categorical variables. Multiple logistic regression models were employed to determine associations between the main outcomes (cognitive impairment and low resilience) and the main covariate (working as HCPs vs. Admins), adjusting for all potential confounders. RESULTS: HCPs showed a significantly greater cognitive impairment, less resilience, and DASS-21 than the Admins. The odds of impaired cognitive function in HCPs were significantly higher than the Admins (odds ratio [OR]: 4.45, 95% confidence interval [CI]: 1.27-15.67, P = 0.020), adjusted for all potential covariates. Similarly, the odds of low resilience in HCPs were significantly higher than Admins (OR: 5.81, 95% CI: 2.72-12.44, P < 0.001), adjusted for all potential covariates. However, the adjusted association between impaired cognitive function and low resilience was not statistically significant (OR: 0.55, 95% CI: 0.23-1.33, P = 0.185). CONCLUSION: HCPs had significantly impaired cognitive function and low work resilience. Workplace policies and interventions to control depression, stress, and anxiety are required as it is the encouragement of physical activity. Programs that combine positive coping skills training (e.g., relaxation training, positive thinking, and problem solving) with resilience-building interventions (e.g., taking a proactive approach to solving problems, being flexible and adaptive) should be developed, with special attention to HCPs who have a higher sense of self-efficacy.